Of syntax and chords; The universal connection of language and music / S. Mariam Md. lliyas - Md. lliyas, S. Mariam (Faculty of Information Management, 2015)
Nowadays, people all around the world see education as a very important aspect in their lives. Regardless of any subject or topic that is being focused into, there are indeed many researches and studies to improve the quality of education. Among all the subjects are music and language. These two subjects are indeed not the same subject; however, I do believe that music and language is interrelated to each other; based on several aspects.